2015
DOI: 10.1002/jaba.227
|View full text |Cite
|
Sign up to set email alerts
|

Data analysis of response interruption and redirection as a treatment for vocal stereotypy

Abstract: Vocal stereotypy, or repetitive, noncontextual vocalizations, is a problematic form of behavior exhibited by many individuals with autism spectrum disorder (ASD). Recent research has evaluated the efficacy of response interruption and redirection (RIRD) in the reduction of vocal stereotypy. Research has indicated that RIRD often results in reductions in the level of vocal stereotypy; however, many previous studies have only presented data on vocal stereotypy that occurred outside RIRD implementation. The curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
64
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 29 publications
(35 reference statements)
6
64
1
Order By: Relevance
“…Despite some research supporting the efficacy of RIRD in decreasing vocal stereotypy, the procedure may be difficult to implement, especially initially, if the individual engages in high levels of stereotypy and thus require frequent intervention (Wunderlich & Vollmer, ). Additionally, RIRD does not always increase appropriate vocalizations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some research supporting the efficacy of RIRD in decreasing vocal stereotypy, the procedure may be difficult to implement, especially initially, if the individual engages in high levels of stereotypy and thus require frequent intervention (Wunderlich & Vollmer, ). Additionally, RIRD does not always increase appropriate vocalizations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the aversive nature of demands used in the overcorrection sequence of the RIRD procedure can evoke additional problem behavior (i.e., vocal stereotypy) in some individuals. Along these lines, Wunderlich and Vollmer () found that most vocal stereotypy occurred for one participant during the RIRD intervention. In Hagopian, Bruzek, Bowman, and Jennett (), rates of problem behavior were compared between control and interruption conditions, the latter involving the interruption of activities with a simple “do” request on a fixed‐time 30‐second schedule.…”
Section: Discussionmentioning
confidence: 95%
“…The goal of the present two‐experiment study was to evaluate the effects of such a manipulation in the form of four, brief (3 seconds) activity interruptions each followed by attention and immediate resumption in the preferred activity just prior to requesting a transition away from preferred activities. It should be noted that the interruptions used in the present study differed in several ways from a punishment procedure for vocal stereotypy known as response interruption and redirection (RIRD; Ahern, Clark, MacDonald, & Chung, ; Wunderlich & Vollmer, ). Response interruption and redirection is implemented with no items or activities present, combines response blocking with a three‐demand overcorrection sequence, is contingent on problem behavior, and involves praise for compliance.…”
mentioning
confidence: 99%
“…It has been suggested that exclusion of such data may overestimate the efficacy of RIRD. This was the finding for some participants whose stereotypy occurred at baseline levels when data were reported and included from implementation intervals (Wunderlich & Vollmer, ). However, evidence for vocal stereotypy suppression when interval data are included was demonstrated by Cividini‐Motta et al ().…”
Section: Discussionmentioning
confidence: 99%